Analisis Daya Saing pada Industri Perbankan di Kota Medan: Digitalisasi Perbankan dengan Pendekatan SWOT - Teddy Wiranata; Nikson Marpaung; Wiwied Risdianto Putri; Salihah Aula Br Sembiring; Fitri Annisa; Sanusi Gazali Pane (LPPM IAI Nasional Laa Roiba Bogor, 2023)
The banking industry in Medan City has experienced significant growth alongside technological advancements and digitalization. This transformation encompasses the utilization of Information and Communication Technology (ICT) to enhance operational efficiency and innovate banking services. While major banks have extensive branch networks and strong reputations, some may face challenges in swiftly adopting new technologies. Significant opportunities lie in expanding digital banking services through investments in mobile applications, cutting-edge technology, and collaborations with local fintech companies. However, competition from digital banks and cybersecurity risks pose noteworthy threats that require attention. SWOT analysis can provide crucial insights for banks in Medan to identify competitive advantages, address weaknesses, and capitalize on strategic opportunities. This research aims to understand the influence of digitalization on the competitiveness of the banking industry in Medan City, identifying strengths, weaknesses, opportunities, and threats, while offering strategic recommendations to sustain and improve positions in this rapidly evolving market. The benefits of this journal include profound comprehension of digitalization's impact, optimized competitive advantages, market adaptation, contributions to local economic growth, regulatory policy guidance, and added value to the community and local economy.